Genotypic and allelic variability of calpain CAPN1-316 gene in Tropical Milking Criollo cattle - Torres-Beltrán, Anayeli; Becerril-Pérez, Carlos M; Calderón-Sánchez, Francisco; Morales-Trejo, Fredy; Hernández-Cázares, Aleida S; Rosendo-Ponce, Adalberto (Revista Colombiana de Ciencias Pecuarias, 2024)
Background: Genes and their variants associated with milk and beef production traits in cattle can be identified through molecular markers. Calpain gene CAPN1-316 has been associated with meat tenderness in several breeds. Tropical Milking Criollo males not selected as breeders are usually destined to commercial beef production. Objective: To estimate genotypic and allelic frequencies of calpain CAPN1-316 gene -associated with meat tenderness- in Tropical Milking Criollo cattle breed. Methods: Molecular marker microsatellites of single sequence repeats (SSR) from DNA were extracted from blood samples of 423 purebred animals from three farms to identify variants of CAPN1-316 using polymerase chain reaction (PCR). Genotypic and allelic frequencies within populations, genetic distance, heterozygosity, and Xi squared (X2) test were performed using POPGENE software. Results: Genotypic frequencies of the whole population were CC 0.31, GG 0.18, and CG 0.51. Allelic frequencies of variant C per farm were 0.62, 0.60, and 0.52. Genotypic and allelic frequencies of the CAPN1-316 polymorphisms were in Hardy-Weinberg equilibrium (X2, p>0.05). The CC genotype showed indication of greater meat tenderness. Conclusion: The C variant of CAPN1-316 gene -favorable to meat tenderness- has higher frequency than the G variant in Tropical Milking Criollo cattle.